Engineering the migration and attachment behaviour of primary dermal fibroblasts. Issue 5 (28th January 2019) - García‐Gareta, Elena; Levin, Alexandra; Hook, Lilian
Abstract: The availability of primary cells present in pathological conditions is often very limited due to stringent ethical regulation and patient consent. One such condition is chronic wounds, where dermal fibroblasts show a deficient migration. In vitro models with cellular tools that mimic the in vivo scenario would be advantageous to test new therapies for these challenging wounds. Since the availability of primary dermal fibroblasts present in chronic wounds is restricted and their "shelf‐life" limited due to the increased senescence, our aim was to engineer human dermal fibroblasts with impaired migration using synthetic Arg‐Gly‐Asp (RGD) peptides. We studied fibroblast behaviour on three different two dimensional (2D) surfaces, representative of the dermal extracellular matrix and the materials used in the development of dermal scaffolds, in addition to commercially available, collagen‐based 3D dermal scaffolds, demonstrating that the concentration of synthetic RGD peptides necessary to impair migration of dermal fibroblasts should be tailored to the particular surface/material and cell population used. The described technology could be translated to other cell types including established cell lines. A wide range of synthetic peptides exists, which differ in the amino acid sequence, thus increasing the possibilities of this technology. Abstract : The availability of primary cells present in pathological conditions such as chronic wounds is often very limited. This study presents an engineered cell population that was shown to behave like fibroblasts in delayed wound healing, in terms of attachment and migration, on both 2D surfaces and 3D matrices.